Diastereoselective Synthesis of Pyranoquinolines on Zirconium‐Containing UiO‐66 Metal‐Organic Frameworks. Issue 27 (25th July 2016) - Rechac, Víctor L.; Cirujano, Francisco G.; Corma, Avelino; Llabrés i Xamena, Francesc X.
Abstract : The Zr terephthalate MOFs UiO‐66 and UiO‐66‐NH2 have been found to be highly diastereoselective catalysts for the synthesis of a pyrano[3, 2‐ c ]quinoline through an inverse electron‐demand aza‐Diels–Alder [4+2] cycloaddition of an aryl imine (formed in situ from aniline and benzaldehyde) and 3, 4‐dihydro‐2 H ‐pyran in one pot, affording the corresponding trans isomer in diastereomeric excesses of 90–95 %. The solids are stable under the reaction conditions and can be reused at least three times without significant loss of activity or diastereoselectivity. Abstract : Zirconium‐containing UiO‐66‐type compounds catalyze the Povarov reaction between an imine and dihydropyran at room temperature to give trans ‐pyrano[3, 2‐ c ]quinoline with diastereomeric excesses of 90–95 %. The solids are stable and reusable catalysts that show no significant loss of activity or diastereoselectivity.